What Is Not Named, Does It Exist? Ethnolinguistic Visibility in the 2022 Census in Argentina - De Mauro, Sofía (Íkala, Revista de Lenguaje y Cultura, 2025)
This research article presents some lines of interpretation regarding the ethnolinguistic survey in the 2020 Census (2022) in Argentina, consisting of three questions. The first one, an open-ended question on Indigenous self-recognition was addressed to the entire population—a milestone in the country’s census history. The second and third ones—dependent on the answer to the first one—inquired about the name and language of those people, respectively. This research article focused on that glottopolitical event, developing an analysis by revisiting three areas of interest. Firstly, a brief history of censuses in the country will be recounted, with an emphasis on the process in the last few years at the Latin American and national levels, following the adherence to the International Labor Organization’s 169 Convention that established free and informed consultation. Secondly, we will analyze how the question on Indigenous languages was incorporated in 2022 and the census process, in line with the paradigm of linguistic rights, the ideology of “access,” and the ideology that supports the univocal link between people, culture, and language. Thirdly, we will explore some glottopolitical dimensions for the discussion on consultation and ethnolinguistic visibility, as an instrument of both the state and activists. This article examines the glottopolitical dimensions of censuses as input for linguistic revitalization and as a reflection of linguistic ideologies, while warning of the risk of superficial accounting, based on misleading criteria, for Indigenous languages.